Waning immunity of one-dose measles-mumps-rubella vaccine to mumps in children from kindergarten to early school age: a prospective study - Yuanbao Liu; Zhihao Liu; Xiuying Deng; Ying Hu; Zhiguo Wang; Peishan Lu; Hongxiong Guo; Xiang Sun; Yan Xu; Fenyang Tang; Feng-Cai Zhu (Taylor & Francis Group, 2018)
Background: In China, one dose measles-mumps-rubella vaccine (MMR) was administered to children aged 18-24 months. The mumps incidence was still high. Data on the waning immunity to mumps after MMR vaccination are limited. This study aimed to describe the waning immunity to mumps in kindergarten and primary school children to provide a scientific basis for confirming an optimal age for a second dose. Methods: An observational, prospective study on one-dose MMR in children in kindergarten and primary school was conducted from 2015 to 2016. Waning immunity to mumps in terms of seropositivity and geometric antibody concentration (GMC) with time was analyzed. Results: In total, 7436 eligible subjects in kindergarten (3435) and primary school (4001) were included in 2015. The overall GMC (201.7 U/ml) and seropositivity (75.4%) to mumps antibodies in 2016 were significantly lower compared to those in 2015 (218.7 U/ml, 78.4%). Asymptomatic infection occurred within one year in 8.8% of children who received one-dose MMR. Conclusions: Children who received one-dose MMR in kindergarten and primary school were at high risk of mumps infection, and waning immunity occurred with time. Determining the optimal age for the second dose of MMR in children should be prioritized to prevent mumps epidemics.